Growth Of Alxga1-Xn Thin Films On Silicon Using Sol-Gel Spin Coating Technique - Isa, Nurul Atikah Mohd (2018)
Group-III nitrides such as aluminum nitride (AlN) and aluminum gallium nitride (AlGaN) have potential applications for ultraviolet light emitting devices and high power devices. Nowadays, sophisticated and expensive growth techniques are used to synthesize these thin films. Thus, an alternative method known as sol-gel spin coating method which is relatively cheap and simple as well as less explored was used to grow AlN and AlGaN thin films. In this work, the growth and characterization of AlN thin films on silicon (Si) substrate by sol-gel spin coating method under various nitridation parameters such as nitridation temperatures, nitridation durations, and ammonia (NH3) gas flow rates were investigated. For different nitridation temperatures, it was found that the full width at half maximum (FWHM) of AlN(002) diffraction peak of X-ray diffraction (XRD) and the E2(high) peak of Raman decreased, as the nitridation temperature increases from 1100 to 1150°C, which indicates the improvement of AlN crystal quality. The FWHM of both XRD and Raman increases when the nitridation temperature increased to 1200°C. This implied the degradation of AlN crystal. Moreover, the field-emission scanning electron microscopy (FESEM) image of sample nitridated at 1150°C showed a smooth and uniform surface with slightly bigger and densely packed grains as compared with that nitridated at 1100°C. As for nitridation durations, XRD showed the improvement of crystalline quality of AlN with increasing nitridation duration from 45 to 60 min.